The Interplay of Fiqh, Adat (Customary Law), and State Law in Inheritance Cases: A Study in the Minangkabau Community of West Sumatra - Md Shodiq; Nina Anis; Faisal Razak (Journal of Noesantara Islamic Studies, 2025)
Inheritance in the Minangkabau community of West Sumatra represents a complex legal phenomenon that reflects the coexistence and tension between fiqh (Islamic jurisprudence), adat (customary law), and state law. This study aims to analyze how these three normative systems interact, overlap, and negotiate authority in resolving inheritance disputes among Minangkabau people. Using a qualitative sociolegal approach, the research was conducted through indepth interviews, field observations, and document analysis of inheritance cases handled by both adat institutions and religious courts. The findings reveal that inheritance practices in Minangkabau are shaped by a hybrid legal culture: adat prioritizes matrilineal lineage and communal ownership, fiqh emphasizes individual entitlement based on Qur’anic prescriptions, while state law seeks harmonization through formal judicial mechanisms. In practice, local communities often employ adat principles for land and property distribution but rely on fiqhbased settlements when disputes escalate to formal courts. The study concludes that the coexistence of these systems demonstrates a dynamic legal pluralism, where social harmony is maintained through pragmatic compromise rather than rigid adherence to a single legal framework.